2021
DOI: 10.7150/jca.53983
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cysteine Protease Inhibitor CST2 as a Potential Biomarker for Colorectal Cancer

Abstract: Additional biomarkers for the development and progression of colorectal cancer (CRC) remain to be identified. Hence, the current study aimed to identify potential diagnostic markers for CRC. Analyses of cysteine protease inhibitor [cystatins (CSTs)] expression in CRC samples and its correlation with cancer stage or survival in patients with CRC demonstrated that CRC tissues had greater CST1 and CST2 mRNA expression compared to noncancerous adjacent tissues, while higher CST2 mRNA expression in CRC tissues was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In our previous study, we confirmed and substantiated that CST2 RNA levels were inversely correlated with clinical data in the database. Unexpectedly, we discovered that CST2 was markedly expressed in tissues and exerted an anticancer effect (Xie et al 2021 ). Furthermore, the literature lacks information on CST2 protein expression in GC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we confirmed and substantiated that CST2 RNA levels were inversely correlated with clinical data in the database. Unexpectedly, we discovered that CST2 was markedly expressed in tissues and exerted an anticancer effect (Xie et al 2021 ). Furthermore, the literature lacks information on CST2 protein expression in GC tissues and cells.…”
Section: Discussionmentioning
confidence: 99%
“…CSTB is a protease inhibitor of cathepsin that is increased in cancer and acts as an intracellular thiol protease inhibitor [ 73 , 74 ]. Evidence suggests the role of CSTB in various diseases [ 46 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the epithelial and mesenchymal transition (EMT) and TGF-β signaling can be induced by CST2 in gastric cancer, which can promote metastasis and tumor progression [41]. CSTs have also been suggested as a prognostic biomarker for various cancers [57][58][59]. CST4, known as cystatin SA, was also founded highly expressed in gastric and colorectal cancer to promote cell proliferation, invasion, and metastasis [42,60].…”
Section: Discussionmentioning
confidence: 99%